The C-Band All-Sky Survey (C-BASS): constraining diffuse Galactic radio emission in the North Celestial Pole region - Dickinson, C; Barr, A; Chiang, HC; Copley, C; Grumitt, RDP; Harper, SE; Heilgendorff, HM; Jew, LRP; Jonas, JL; Jones, ME; Leahy, JP; Leech, J; et al. (Oxford University Press, 2019)
The C-Band All-Sky Survey (C-BASS) is a high sensitivity all-sky radio survey at an angular resolution of 45 arcmin and a frequency of 4.7 GHz. We present a total intensity map of the North Celestial Pole (NCP) region of sky, above declination >+80°, which is limited by source confusion at a level of ≈0.6 mK rms. We apply the template-fitting (cross-correlation) technique to WMAP and Planck data, using the C-BASS map as the synchrotron template, to investigate the contribution of diffuse foreground emission at frequencies ∼20–40 GHz. We quantify the anomalous microwave emission (AME) that is correlated with far-infrared dust emission. The AME amplitude does not change significantly (⁠<10 per cent⁠) when using the higher frequency C-BASS 4.7 GHz template instead of the traditional Haslam 408 MHz map as a tracer of synchrotron radiation. We measure template coefficients of 9.93 ± 0.35 and 9.52±0.34 K per unit τ353 when using the Haslam and C-BASS synchrotron templates, respectively. The AME contributes 55±2μK rms at 22.8 GHz and accounts for ≈60 per cent of the total foreground emission. Our results show that a harder (flatter spectrum) component of synchrotron emission is not dominant at frequencies ≳5 GHz; the best-fitting synchrotron temperature spectral index is β = −2.91 ± 0.04 from 4.7 to 22.8 GHz and β = −2.85 ± 0.14 from 22.8 to 44.1 GHz. Free–free emission is weak, contributing ≈7μK rms (⁠≈7 per cent⁠) at 22.8 GHz. The best explanation for the AME is still electric dipole emission from small spinning dust grains.